2009
DOI: 10.1016/j.trim.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A role for regulatory T cells in renal acute kidney injury

Abstract: Ischemia reperfusion injury (IRI) is a potential contributor for the development of chronic allograft nephropathy. T cells are important mediators of injury, even in the absence of alloantigens. We performed a depletion of TCD4(+)CTLA4(+)Foxp3(+) cells with anti-CD25(PC61), a treatment with anti-GITR (DTA-1) and rat-IgG, followed by 45 min of ischemia and 24/72 h of reperfusion, and then analyzed blood urea, kidney histopathology and gene expression in kidneys by QReal Time PCR. After 24 h of reperfusion, depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
1
31
0
4
Order By: Relevance
“…33 When PC61 was administered 24 hours before IRI (not far enough in advance to achieve maximal FoxP3 + Treg depletion at the time of injury), BUN levels and ATN were not different at 24 hours but significantly elevated compared with control antibody-treated mice at 72 hours after ischemia. 34 Furthermore, administration of the immunosuppressant mycophenolate mofetil in WT mice but not T cell-deficient mice inhibited recovery from renal IRI. 35 The impaired recovery from IRI in WT mice was associated with a dramatic reduction in Treg trafficking into the kidney.…”
Section: Promotion Of Recovery After Akimentioning
confidence: 99%
“…33 When PC61 was administered 24 hours before IRI (not far enough in advance to achieve maximal FoxP3 + Treg depletion at the time of injury), BUN levels and ATN were not different at 24 hours but significantly elevated compared with control antibody-treated mice at 72 hours after ischemia. 34 Furthermore, administration of the immunosuppressant mycophenolate mofetil in WT mice but not T cell-deficient mice inhibited recovery from renal IRI. 35 The impaired recovery from IRI in WT mice was associated with a dramatic reduction in Treg trafficking into the kidney.…”
Section: Promotion Of Recovery After Akimentioning
confidence: 99%
“…4 Our group and others have demonstrated the role of different immune cell populations in kidney IRI. [5][6][7][8][9] Recently, an intimate connection between the intestine and the kidneys has been proposed. 10,11 Established data have already shown that modification of microbiota composition could affect the outcome of glomerulopathies, and recent data indicate that renal inflammation is associated with the production of uremic toxins by the intestine and with augments intestinal permeability, leading to the onset of systemic inflammation.…”
mentioning
confidence: 99%
“…Reduction in numbers of Tregs predisposed mice to tubular necrosis, renal infl ammation and loss of function [37]. In other studies, Treg depletion prior to more severe ischemia also worsened renal injury measured at 72 h of reper fusion [38]. Th ese results suggest that enhancement of Treg numbers or function may be an eff ective preventative therapy for AKI.…”
Section: Protective Actions Of Regulatory T Cellsmentioning
confidence: 74%